"More of a Training Film": Watching Fictional Outbreak Narratives during the Covid-19 Pandemic. Issue 2 (15th March 2022) - Edgar, Amanda Nell; Dechant, Aaron M.; Eakin, Catherine
ABSTRACT: Using interviews with twenty-eight people who watched fictional outbreak narratives early in the Covid-19 pandemic, we argue that the genre helped viewers process the abstract uncertainty of the time through concrete sound and imagery. Viewers used critical distance to separate the real life horrors of the moment and the mediated "horrors" of the films. In doing so, audiences simultaneously pulled the films close to build their own pandemic grammar and held the films at a distance to reassure themselves about their own – and society's – odds for survival. This approach to media selection and consumption has implications for media studies during times of collective trauma, as it demonstrates the ways narratives about suffering inform social response in sometimes unexpected ways.